Analisis Perancangan Bisnis Usaha Peternakan Burung Lovebird - Utomo, Andhika Ngesti; , Much. Djunaidi, ST, MT (2016)
Chirping bird hobbyist may already no stranger to hear the names of birds lovebird. The increasing demand for bird species is characterized by the many races of birds chirping in the various regional and national level that makes lovebird as the main class. This condition can be used to find an advantage by breeding or cultivation of a bird lovebird. The purpose of this research is to know the market opportunities and create business concepts, determine the location and layout (layout) lovebird bird breeding business, designing the management of production processes, analyze the feasibility and investment criteria lovebird bird breeding business. In making this business concept using the Business Model Canvas. To analyze the financial aspects of using the Net Present Value, Internal Rate of Return, and Profitability Index. The advantages of the farm are the lovebird bird chicks that have long duration chirping sound quality. The results of the analysis of aspects of the market indicate that potential lovebird bird breeding business is still a big chance in the future. The results of the calculations in the financial aspects of using the Net Present Value positive value 294,887,660, Internal Rate of Return is 53%, and Profitability Index by 1.89. It can be concluded that the lovebird bird breeding business is feasible and profitable.